(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to explain the Work Motivation of Officials Women’s Empowerment and Child Protection (DP3A) in Enrekang Regency. This study used qualitative research. data collection techniques used the instrument of interview, observation and literature study. The data were analyzed in an interactive manner continuously until the data obtained was saturated. The Result of this study showed that the Employee Work Motivation of the Empowerment Service Women and Child Protection (DP3A) were good but still existed some employees who had low motivation in implementing task due to a lack of awareness in themselves to carry out the task as well as they should be. So that the employees work motivation needs good social relations, creating an atmosphere good work, implemented a reward program, and provided deep tags work. Keywords: motivation, work, employees.